PREVALENCE OF VIRAL INFECTIONS AMONG THE DRUG ADDICTS IN LIBYA (مجلة البحوث الأكاديمية, 2016)
drug users are at high risk for direct exposure to a variety of blood-borne bacterial and viral infections. Accurate up-to-date data on the extent of drug use and the prevalence of blood-borne viruses among the illegal drug users are a necessary pre-requisite for health and social service planning and policy development. Study aims to estimate the prevalence of the viral infections among drug addicting patients and also to examine the interrelationship between the presence of these blood-borne viral infections and socio-demographic characteristics among the drug users. Blood samples were collected from 479 respondents and all were analysed for the seropositivity for HBV, HCV and HIV with ELISA kit (Dialab GMBH, Austria).